Management accounting - Lucey, T. (London : DP Publications, 2003)
This revised fifth edition provides a thorough understanding of the subject, principally for students preparing themselves for professional examinations but also for managers who need to communicate with members of the accounting profession.
Includes index.
oif 27/03/15
Loan
Keywords: Managerial accounting; Management accounting; Accounting; Financial management; Management Planning; Decision making